The Indications of Amniocentesis for the Diagnosis of Aneuploidy among Pregnant Women - Fatemeh Golshahi; khoosheh khaleghinezhad; Behrokh Sahebdel; Nafiseh Saedi; Zohreh Salari (Mashhad University of Medical Sciences, 2024)
Amniocentesis is one of the known and accessible methods for prenatal diagnosis, which is performed for various reasons during pregnancy. The present study was performed to determine the most common reasons for amniocentesis to detect aneuploidy. This retrospective cohort study was performed on the records of 635 pregnant women who underwent amniocentesis guided by high-resolution ultrasound during 2010-2019 at Yas Hospital of Tehran University of Medical Sciences, Tehran, Iran. The study evaluated the indications for amniocentesis in order to investigate the relationship between each of these indications and fetal aneuploidy results. All participants were evaluated for genetic study results. The prevalence of aneuploidy was 8.2% and abnormal screening test was the most common reason for performing amniocentesis (68% of cases). Also, abnormal ultrasound results had the strongest correlation with the possibility of genetic abnormalities in the current pregnancy. Therefore, amniocentesis is highly recommended for women with indications, especially in cases of abnormal ultrasound results.